Comparison of the Optical Efficiency of Two Designs of the Maksutov–Cassegrain Telescope - Badr, Alaa; Marwa W. Abdulrahman; Sameer H. R. Aldeen (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2024)
The research aims to develop the best possible design for the widely used Cassegrain telescope. The system consists of two models of different designs: (a) the telescope consists of a Maksutov lens, a spherical primary mirror, and a secondary mirror attached to the lens; (b) it consists of a Maksutov lens and a spherical primary mirror, plus a non-lens attached secondary mirror located between the lens and the primary mirror. The image was evaluated and analyzed using the analysis tools in Zemax software. The results of the two designs showed that the telescope whose secondary mirrors are not adjacent to the Maksutov lens produces high quality image that is almost free from aberration, and then comes the telescope whose secondary mirrors are adjacent to the Maksutov lens in terms of image quality. In the first design, the tangential and sagittal axes in the MTF function of the remaining angles (0.1, 0.2, 0.3, 0.4, and 0.5) contain two curves, which show how the loss of symmetry has changed the value of the function for the two axes. In the second design, the sagittal and tangential axes are identical in the angles of incidence (0, 0.1, and 0.2), and the transverse and sagittal axes of the remaining angles (0.3, 0.4, and 0.5) contain two curves. In PSF for the first design, there are several pretty high peaks on the surface of the image at the angle of incidence (0, 0.1). Since the shape is regular, the point spread function indicates that there isn't an aberration, but in terms of the angles (0.2, 0.3, 0.4, 0.5), we observe a gradual loss in intensity and the appearance of elevations on both sides of the picture. In the second design, at the angles (0, 0.1, 0.2, 0.3), we observe in Figure 5 that there are several high peaks free from aberration.